2018
DOI: 10.1177/0961203318804885
|View full text |Cite
|
Sign up to set email alerts
|

Urinary B-cell-activating factor of the tumour necrosis factor family (BAFF) in systemic lupus erythematosus

Abstract: Introduction We examined the clinical relevance of urinary concentrations of B-cell–activating factor of the tumour necrosis factor family (BAFF) and a proliferation-inducing ligand (APRIL) in systemic lupus erythematosus (SLE). Methods We quantified urinary BAFF (uBAFF) by enzyme-linked immunosorbent assay in 85 SLE, 28 primary Sjögren syndrome (pSS), 40 immunoglobulin A nephropathy (IgAN) patients and 36 healthy controls (HCs). Urinary APRIL (uAPRIL) and monocyte chemoattractant protein 1 (uMCP-1) were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Therefore, it is necessary to identify non-invasive biomarkers that can be easily obtained and reflect current renal inflammation [ 34 ]. Over the last two decades, many clinical studies have demonstrated the presence of molecules associated with B-cell activation in the serum [ 29 , [35] , [36] , [37] ] and kidney tissues [ 24 , 26 , 28 , 38 ] of active LN patients. One study demonstrated that serum BAFF level was lower in SLE patients with nephrotic-range proteinuria than in SLE patients with less severe proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is necessary to identify non-invasive biomarkers that can be easily obtained and reflect current renal inflammation [ 34 ]. Over the last two decades, many clinical studies have demonstrated the presence of molecules associated with B-cell activation in the serum [ 29 , [35] , [36] , [37] ] and kidney tissues [ 24 , 26 , 28 , 38 ] of active LN patients. One study demonstrated that serum BAFF level was lower in SLE patients with nephrotic-range proteinuria than in SLE patients with less severe proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Like BAFF, APRIL has been investigated as a non-invasive prognostic biomarker for severe LN [ 29 ]. Expression levels of APRIL mRNA were significantly higher in glomeruli and the tubulointerstitial compartment of biopsy samples from patients with proliferative LN compared to controls as measured by real-time PCR [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNFSF13B is also known as a lymphocyte B stimulator or B-cell activating factor (BAFF), in reference to its involvement in the activation, proliferation, and differentiation of this type of cell [15]. The impairment of TNFSF13B has been described in autoimmune diseases such as systemic lupus erythematosus [17], Sjögren syndrome [17, 18], and especially, rheumatic diseases [19], although always with significantly higher levels than the healthy controls. BAFF (TNFSF13B) is defined as a function regulator of B and T cells, with proinflammatory and anti-inflammatory effects [15, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of the steroid-sparing effects of belimumab may have contributed to rapid tapering of glucocorticoid doses, which in turn unveiled renal activity. Belimumab binds to the soluble counterpart of BAFF, a molecule implicated in the pathogenesis of LN [ 20 , 21 ], and has been shown to alter absolute and relative numbers of B cell subsets, mainly B cells of early developmental stages [ 22 , 23 ]. However, the long-term consequences of BAFF inhibition, e.g.…”
Section: Discussionmentioning
confidence: 99%